2008
DOI: 10.3138/physio.60.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Use of Outcome Measures in Physiotherapy Practice in Ireland from 1998 to 2003 and Comparison to Canadian Trends

Abstract: Purpose: The purposes of this study were to examine changes in the use of standardized outcome measures by practising physiotherapists in Ireland and to compare those trends to the results of a similar survey conducted previously in Canada. Method: A survey methodology was employed. The review of practice occurred at two points in time. Senior clinical physiotherapists working with older people participated. Questions were asked about the use of standardized outcome measures, the nature and pattern of their us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 21 publications
3
23
0
6
Order By: Relevance
“…Kay and colleagues reported on a Canadian survey conducted back in 1998 (Kay et al ., ) that showed that on admission and discharge from hospital, 85% of participating physiotherapists stated that they measured range of motion or applied manual muscle tests; however, compliance dropped when reporting about pain using a visual analogue scale (67%) or the Berg Balance Scale (BBS) for balance (63%). Stokes and O'Neill re‐conducted the Kay et al survey in 2003 in Ireland (Stokes and O'Neill, ) and compared the results. The use of standardized outcome measures appeared to be common practice for evaluating mobility and balance, but for gait, exercise tolerance, stroke and Parkinson's disease, their use was not regularly incorporated into daily practice.…”
supporting
confidence: 55%
“…Kay and colleagues reported on a Canadian survey conducted back in 1998 (Kay et al ., ) that showed that on admission and discharge from hospital, 85% of participating physiotherapists stated that they measured range of motion or applied manual muscle tests; however, compliance dropped when reporting about pain using a visual analogue scale (67%) or the Berg Balance Scale (BBS) for balance (63%). Stokes and O'Neill re‐conducted the Kay et al survey in 2003 in Ireland (Stokes and O'Neill, ) and compared the results. The use of standardized outcome measures appeared to be common practice for evaluating mobility and balance, but for gait, exercise tolerance, stroke and Parkinson's disease, their use was not regularly incorporated into daily practice.…”
supporting
confidence: 55%
“…Standardized measures, in particular, are important physiotherapy tools, and their use is positively associated with patient outcomes. 17 A recent survey of 369 Ontario PTs 18 reported that the majority of respondents regularly assessed many components of balance and used at least one standardized balance measure in their practice. However, the self-report assessments used in the survey may have overestimated actual performance, 19 and there was no attempt to verify how respondents assessed each component of balance.…”
mentioning
confidence: 99%
“…4 A more recent study in Ireland provided similar findings: lack of time was the most commonly reported barrier to use. 68 Abrams et al found that 80% of the reported barriers to OM use, identified by clinicians, were related to time taken to administer and lack of familiarity with the OM. 65 Copeland has undertaken a study of outcome measures use for patients with low back pain amongst New Zealand physiotherapists.…”
Section: Barriers To Usementioning
confidence: 99%